Aging Is Not Enough to Be Healthy Alone: Combating Aging Through “Gokil Muscle Exercise” - Christiana, Metta; Muhaimin, Ahmad; Nawangsih, S.K.; Eka Kartika, Shinta (Society : Jurnal Pengabdian Masyarakat, 2026)
Aging is an inevitable biological process that significantly affects physical, psychological, and social functions, particularly among individuals aged 40 years and older. In many communities, aging is commonly perceived as a condition that merely requires the absence of disease, without adequate attention to muscle strength, mobility, and functional independence. This community service program was conducted in Bangetayu Kulon Village, Semarang, Indonesia, to improve the quality of life of middle-aged and elderly residents through an innovative physical activity intervention known as Gokil Muscle Exercise. The program aimed to increase participants’ knowledge, awareness, and practical skills related to muscle strengthening as a strategy to prevent sarcopenia and functional decline. The activities included health education, interactive discussions, pre-test and post-test assessments, and guided exercise training using a combination of seated and standing movements accompanied by cheerful music. A total of 66 participants aged 31–63 years participated in the program. The results demonstrated a significant improvement in participants’ understanding of sarcopenia, its consequences, and appropriate preventive strategies. Participants also reported increased enthusiasm, enjoyment, and motivation to engage in regular physical activity. The findings suggest that being “healthy” alone is insufficient for successful aging; muscle strength and functional fitness are essential components of healthy aging. The Gokil Muscle Exercise program proved to be a feasible, enjoyable, and effective approach to enhancing physical awareness and promoting active aging in the community.